(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This article critically explores the assumptive frameworks underpinning current psychopathological conceptualisations of paranoid/persecutory delusions, which position such experiences as false and meaningless phenomena. An existential-phenomenological reconceptualisation is provided as an alternative formulation that allows for recapturing the contextual, relational and subjective nuances in theoretical understanding and therapeutic practice.